Integration of a Grid-Forming MVDC-System into a Transmission Grid Section for Real-Time Applications - Richter, Julian; Burlakin, Ilya; Wagner, Timo; Richter, Michael; Mehlmann, Gert; Luther, Matthias (8th IEEE Workshop on the Electronic Grid (eGrid 2023), 2023)
MVDC systems offer the possibility of bulk integration of renewable energies coupled at suitable nodes in transmission grids. However, some challenges still need to be solved for commercial use, such as appropriate control of the converter stations and interactions with existing AC equipment. This paper proposes a methodology to create a real-time AC Study Area with plausible short-circuit power and generically adjustable inertia provided by the surrounding area of an extended transmission network using dynamic External Area machines. An MVDC system with grid-forming control is installed in the Study Area, and the behavior of the MVDC system and the External Area machines is analyzed during frequency events at different grid strengths.<br
Keywords: MVDC; Grid-forming Control; Short-Circuit Power; Inertia